Total Phenolic, Flavonoid, and LC-MS Analysis of the Ethanolic Extract of Matoa (Pometia pinnata) Leaves from Kudus, Central Java, Indonesia - Adhina Choiri Putri; Tri Novia Yuliana; Meiny Suzery; Agustina Lulustyaningati Nurul Aminin (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2023)
Matoa (Pometia pinnata) is a plant used as a floral identity in Indonesia, especially in Papua. Local people use boiled water from matoa leaves, which is believed to treat hypertension. Matoa leaves are traditionally used as a therapeutic agent for burns and wounds in Indonesia. Phytochemical screening of matoa leaf extract contains secondary metabolite compounds, including flavonoids, steroids, tannins, and saponins. So far, many of these activities have been reported from the polyphenol group. This research aimed to identify the phytochemical composition of matoa leaves from Kudus in the ethanolic extract using LC-MS. The total phenolic content of ethanol extract using the Folin Ciocalteu method was 35.689 ± 0.726 mg GAE/g extract. The total flavonoid content of ethanol extract using the AlCl3 colorimetric method was 1.384 ± 0.012 mg QE/g extract. Twelve compounds could be identified in the ethanol extract of matoa leaves. The phenolic compounds were vanillin, p-hydroxybenzaldehyde, p-Coumaroyl glycolic acid, syringic acid, gallic acid, phenol, and vanillic acid. The flavonoid compounds were identified as epigallocatechin and apigenin -7-O-diglucuronide. The organic compound was identified as jasmonic acid. The aromatic compound was identified as benzene. Besides, tannin compounds were also identified. The major compounds in matoa leaves from Kudus, Central Java, are vanillin, phenol, and benzene.